It's a linear equation in 'y'.
You can solve it like this:
4y + 2 + 7y = 1
Combine the 'y' terms on the left side:
11y + 2 = 1
Subtract 2 from each side:
11y = -1
Divide each side by 11:
y = -1/11
(4y - 1)(y + 2)
if: 2x + 6 = -6 then: 2x = -12 x = -6 if: 5x + 7y = 1 then: 5(-6) + 7y = 1 7y = 31 y = 31/7
7y-8 = 6y+1 7y-6y = 1+8 y = 9
(1, 1)
(-4, -1)
(4y - 1)(y + 2)
-4x + 4y = 1
No.
x=4y+1 x=4y-1 No,they have different solutions.
if: 2x + 6 = -6 then: 2x = -12 x = -6 if: 5x + 7y = 1 then: 5(-6) + 7y = 1 7y = 31 y = 31/7
7y-8 = 6y+1 7y-6y = 1+8 y = 9
y=5.
(1, 1)
No.
(5, 1)
(-4, -1)
(-1, 5)